2021
DOI: 10.3389/fmicb.2021.666100
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Microplastics Exposure on the Acropora sp. Antioxidant, Immunization and Energy Metabolism Enzyme Activities

Abstract: Graphical AbstractThe experiment flow chart of anti-inflammatory and analgesic effects of P. orientale extracts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 78 publications
1
6
0
Order By: Relevance
“…However, significantly positive correlations were observed between the microplastic concentration and E a in the coral host in July, as well as between the microplastic concentration and E c in the coral host in May and July, which manifested the upregulation of coral E a or E c via the elevation of accumulated microplastics in these months. Alterations in energetic metabolism in corals under microplastic threats were reported in a previous study, and a significant decrease in pyruvate kinase activity was observed in the coral Tubastrea aurea after being treated with microplastics for 24 h. 69 The enzyme activities of lactate dehydrogenase and glucose-6-phosphate dehydrogenase were also downregulated in the coral Acropora sp. upon microplastic treatment.…”
Section: Coral Tolerates Accumulated Microplastics By Regulating the ...supporting
confidence: 59%
See 1 more Smart Citation
“…However, significantly positive correlations were observed between the microplastic concentration and E a in the coral host in July, as well as between the microplastic concentration and E c in the coral host in May and July, which manifested the upregulation of coral E a or E c via the elevation of accumulated microplastics in these months. Alterations in energetic metabolism in corals under microplastic threats were reported in a previous study, and a significant decrease in pyruvate kinase activity was observed in the coral Tubastrea aurea after being treated with microplastics for 24 h. 69 The enzyme activities of lactate dehydrogenase and glucose-6-phosphate dehydrogenase were also downregulated in the coral Acropora sp. upon microplastic treatment.…”
Section: Coral Tolerates Accumulated Microplastics By Regulating the ...supporting
confidence: 59%
“…The enzyme activities of lactate dehydrogenase and glucose-6-phosphate dehydrogenase were also downregulated in the coral Acropora sp. upon microplastic treatment . All of these findings collectively revealed that scleractinian corals could regulate energetic metabolism, such as the energy reserve and consumption processes, to maintain an energy balance with algal symbionts.…”
Section: Discussionmentioning
confidence: 68%
“…Plastic particles have been found embedded within the skeletal matrix of both experimental and colonies collected from the wild [79,[88][89][90][91][92]. Two mechanisms by which the particles become trapped within the skeleton have been suggested.…”
Section: Association and Impact On Coral Reef Biotamentioning
confidence: 99%
“…The level of knowledge around the effect of MNPs on corals remains unclear, and further research is required. Many negative impacts have been identified and include host-symbiont relationship, photosynthetic efficiency, tissue necrosis, calcification rates, energy demand, reproductive success and overall fitness [41,79,80,82,83,86,87,89,[92][93][94][95][96][97][98][99]. Perturbation of photophysiology, bleaching and tissue necrosis have been observed in laboratorybased studies in response to exposure to MNPs [79,85,89,96] and may demonstrate coral species-specificity.…”
Section: Association and Impact On Coral Reef Biotamentioning
confidence: 99%
“…In addition, there was evidence that MPs had negative impacts on their symbiotic association (Okubo et al, 2020;Su et al, 2020). All the research suggested that MPs ingestion might have negative physiological (Reichert et al, 2018;Su et al, 2020;Liao et al, 2021;Tang et al, 2021;Xiao et al, 2021) and ecological (Lamb et al, 2018;Saliu et al, 2019;Soares et al, 2020) consequences for corals.…”
Section: Introductionmentioning
confidence: 99%